2019
DOI: 10.1002/adma.201900363
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing of Polarizing Films via the Synergy between Gold Nanorods and Vitrimer

Abstract: Conventional self‐healing is about the recovery of shape and mechanical properties. In contrast, recovery of functional properties is still a great challenge, especially for optical functional materials, as the known self‐healing methods are incompatible with optical properties. By utilizing the synergistic effect between Au nanorods and vitrimer, the alignment of Au nanorods can be achieved in the crosslinked polymer. The optical properties of the resulting polarizing film, such as light transmittance and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Figure 2e illustrates a proposed selfhealing mechanism based on the dynamic carbamate bond in a vitrimer elastomer. [11] The topological structure of the vitrimer network is reconfigured with the exchange reaction of dynamic carbamate bond, granting the material with self-healing ability. With the prolongation of contact time, the probability to reform carbamate bond is increased, resulting in higher recovery efficiency.…”
Section: Synthesis and Characterization Of Vitrimer Elastomermentioning
confidence: 99%
“…Figure 2e illustrates a proposed selfhealing mechanism based on the dynamic carbamate bond in a vitrimer elastomer. [11] The topological structure of the vitrimer network is reconfigured with the exchange reaction of dynamic carbamate bond, granting the material with self-healing ability. With the prolongation of contact time, the probability to reform carbamate bond is increased, resulting in higher recovery efficiency.…”
Section: Synthesis and Characterization Of Vitrimer Elastomermentioning
confidence: 99%
“…Associative transcarbamoylation processes are sluggish for carbamates, and the dissociative reversion of carbamates to isocyanates and alcohols that typically occurs at high temperatures (>200 °C) can be associated with deleterious side reactions . Therefore, repairable PU thermosets based on carbamate bonds invariably demand the implantation of additional catalysts or redundant nucleophilic hydroxyl groups or structure alternation of carbamate bonds. More recently, Xie and co-workers , reported that PU thermosets containing catalytic dibutyltin dilaurate (DBTDL) or polyol based on tertiary amine exhibited a rapid stress relaxation behavior; then, Dichtel and his co-workers reported that Lewis acid can also activate the dynamic exchange of carbamate bonds. Further work has demonstrated that tin-mediated urethane exchange is a common way to achieve stress relaxation and reprocessability for cross-linked PUs. , Although the addition of a catalyst can endow PU with a high degree of plasticity, metal catalysts are commonly toxic and unstable at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…through the reversible depolymerization or exchange reactions of their dynamic cross-links [ 3 , 9 , 10 , 11 ]. So far, a number of CANs based on Michael addition [ 12 , 13 , 14 ], Diels-Alder reaction [ 15 , 16 ], disulfide exchange [ 17 , 18 , 19 ], imine metathesis [ 20 , 21 , 22 ], transesterification [ 23 , 24 , 25 ], olefin metathesis [ 26 , 27 ], silyl ether transalkoxylation [ 28 , 29 ], diketoenamine exchange [ 30 , 31 ], and dioxaborolane metathesis [ 32 , 33 ] have been proposed in the literature. Besides recyclability, many other adaptive properties of CANs were also investigated, such as reconfigurability [ 34 , 35 ], shape memory [ 36 , 37 ], and network topological transformation [ 18 , 25 , 38 ].…”
Section: Introductionmentioning
confidence: 99%